Efektivitas Manajemen Nyeri Farmakologi Pasca Bedah Laparotomi dengan Anestesi Umum: Systematic Literature Review - Sabrina Rizqi Amelia; Made Suandika; Surtiningsih Surtiningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
Laparotomy is a major surgical procedure associated with a high risk of acute postoperative pain. According to Gan (2017), if pain is not properly managed, it can progress to chronic pain. (Toro et al., 2018) reported that severe pain on the first postoperative day is still commonly found in laparotomy patients, while (Small & Laycock, 2020) indicated that moderate to severe pain within the first 24 hours following major surgery remains a significant clinical issue. This study aims to evaluate the effectiveness of pharmacological pain management following laparotomy under general anesthesia, specifically to identify the types of opioid analgesics used, analyze their effectiveness in reducing pain intensity, identify side effects, and examine administration techniques and routes. This study employed a Systematic Literature Review (SLR) method following the PRISMA guidelines. Literature searches were conducted in the PubMed, ScienceDirect, and SpringerLink databases covering the years 2015–2026. The included studies comprised randomized controlled trials (RCTs), cohort studies, and retrospective studies addressing opioid pharmacological pain management in adult patients following laparotomy under general anesthesia. Study quality assessment was performed using the Joanna Briggs Institute (JBI) instrument. A total of 11 studies met the inclusion criteria. The results of the systematic literature review indicate that opioids are effective in reducing postoperative pain following laparotomy under general anesthesia. The most commonly used opioids are morphine, fentanyl, and oxycodone. Of all the opioids reviewed, oxycodone provided the best pain control, while intrathecal morphine was most effective in reducing the need for supplemental opioids during the early postoperative period. Other opioids, such as extended-release dinalbuphine sebacate and tegileridine, are also effective, but the number of studies is still limited. The most common side effects are nausea, vomiting, pruritus, sedation, and dizziness. Pharmacological pain management using opioids is effective in reducing the intensity of postoperative pain following laparotomy under general anesthesia. Morphine, fentanyl, and oxycodone are the most commonly used opioids. Oxycodone and intrathecal morphine have shown good results in improving pain control and reducing the need for supplemental opioids. The selection of opioid type, dosage, and administration technique must be tailored to the patient’s clinical condition to achieve optimal analgesia with minimal side effects.